Estimation of in situ stress from borehole breakout for improved understanding of excavation overbreak in brittle-anisotropic rock - LeRiche, A.; Kalenchuk, K.S.; Diederichs, M.S. (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
During deep tunnelling or mining infrastructure development, the assumed stress state has significant implications on geomechanical design. Remote measurement of the three-dimensional stress state at depth has proven to be a significant challenge and is often assumed from historic tests or the regional tectonic setting. To date, borehole breakout analysis has only provided some assistance for orientation of the principal stresses in the plane perpendicular to the borehole axis. This paper presents a stress estimation methodology using numerical modelling, which allows for the back analysis of breakout profiles from a shaft pilot hole at KGHM’s Victoria project in Sudbury, Canada. By iteratively changing the horizontal principal stress ratio and maximum tangential wall stress, a set of generalised curves relating breakout characteristics (breakout depth and opening angle) and borehole strength along the 2 km borehole were made. By recording the change in breakout geometry along the length of the hole, the curves can be used to gain an understanding of changes in stress state as a function of depth and lithology. Given the foliated nature of the units intersected throughout the borehole, the effects of systematically oriented structure on breakout was assessed. This provides a relative understanding of how such structure may cause an overestimation of stress from the back analysis of breakout. With the choice of an appropriate constitutive model, characterisation of the full stress tensor through back analysis of borehole scale failure was made with a greater degree of confidence.